Distributional consequences of labor-demand shocks: The 2008-09 recession in Germany - Olivier Bargain; Herwig Immervoll; Andreas Peichl; Sebastian Siegloch (Center for Economic Studies and ifo Institute (CESifo), 2011)
The distributional consequences of the recent economic crisis are still broadly unknown. While it is possible to speculate which groups are likely to be hardest-hit, detailed distributional studies are still largely backward-looking due to a lack of real-time microdata. This paper studies the distributional and fiscal implications of output changes in Germany 2008-09, using data available prior to the economic downturn. We first estimate labor demand on 12 years of detailed, administrative matched employer-employee data. The distributional analysis is then conducted by transposing predicted employment effects of actual output shocks to household-level microdata. A scenario in which labor demand adjustments occur at the intensive margin (hour changes), close to the German experience, shows less severe effects on income distribution compared to a situation where adjustments take place through massive layoffs. Adjustments at the intensive margin are also preferable from a fiscal point of view. In this context we discuss the cushioning effect of the tax-benefit system and the conditions under which German-style work-sharing policies can be successful in other countries.
Keywords: D58; J23; H24; H60; 330; labor demand; output shock; tax-benefit system; crisis; income distribution; Konjunktur; Wirtschaftskrise; Arbeitsnachfrage; Schock; Verteilungswirkung; Arbeitszeitflexibilisierung; Lohnersatzleistungen; Beschäftigungseffekt; Deutschland